Small Sided Games as an Innovative Strategy in Football Coaching in Junior High School - Kholiqulhuda, Richi Awa; Mochamad Ridwan; Sapto Wibowo (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Learning soccer in junior high schools (SMP) still experiences several problems. Some of them are low student participation, the use of a dominant conventional approach, and the lack of contextual and fun method choices. This causes students to master the basic techniques of the game less effectively. The purpose of this study was to determine how effective the use of Small Sided Games (SSG) is as a creative approach to teaching early age soccer in junior high schools. Quantitative methods were used, with a quasi-experimental pretest-posttest non-equivalent group design. 40 students of grade VIII were the subjects. They were divided into two groups: one that conducted an experiment with SSG, and the other that conducted a control with a conventional method. A validated and reliable basic soccer technique skill observation sheet was the research instrument. The results showed that the experimental group obtained an average increase in score from 60.0 to 64.8, while the control group only obtained an increase in score from 59.3 to 59.6. Both experimental groups showed significant improvements, each with p < 0.001 and Cohen's d = 0.876, according to the t-test. The result is that SSG-based learning improves students' basic soccer skills better than conventional methods. In addition, SSG-based learning can serve as a strategic alternative for physical education in junior high schools.